Moral Philosophical Thought from Greece and Islam (Journal of Human Sciences, 2020)
Morality represents value and a cornerstone in the topic of values, as it occupies the supreme rank, for man is unique from others with mental contemplation, so he is able to retire his reality and start looking at it, and transcending it, in light of a higher ideal that he owes loyalty to.   The aim of this study (Moral Philosophical Thought from Greece and Islam) is to consider a number of problems presented to us by the study, through which we seek to direct human behavior towards the moral act, and we draw attention to it to distinguish between the moral act from other human actions. We also highlight ethics of knowledge about whether it is acquired or innate from the point of view of Greek and Islamic philosophy. Moreover, which is more useful in organizing and correcting human behavior. What is the vision of Islam in that? And in view of the great role that it plays in evaluating human life, and because of the importance and role of ethics in the human personality because of related elements such as thought, emotion, instinct and will and its role in organizing and controlling these elements, we see it necessary to study the concept of ethics to know its implications and meanings, as well as for consideration and search for the reasons for the difference starting from the concept and motives, and knowing which one of them is more elevating the human life to make it the guide in the right path of life. To reach these goals, we need an approach that guarantees access to those results. The nature of the topic here imposes on us the adoption of two basic approaches, which are the analytical approach and the comparative approach, along with other approaches such as historical and others according to what the nature of the topic dictates to us. Then the study was concluded with a conclusion, through which we affirm that the nature of moral and mental morals is the same in its motives and goals as it seeks to consider the nature of the human person with all impartiality and respect to provide the conditions for his/her happiness, even if the approaches differ. God Almighty before the religious approach (the Holy Qur’an) is deposited in a person, In him/her the mind was deposited the container that is tight and aware of this, as we note in a large number of verses of the Holy Qur'an that address the mind. For example, do you not understand, do you not see .. and my success is only in God, the Mighty and the Wise.